Dynamic Increase in China's Outward Foreign Direct Investment in the Years 2007-2009 and its Investment Position in the Light of Dunning's Theory - Konieczny, Dominik (Wzrost wartości chińskich inwestycji zagranicznych w latach 2007-2009 a pozycja inwestycyjna ChRL w świetle teorii ścieżki inwestycyjno-rozwojowej J.H. Dunninga, 2010)
Observation of the stage of development of People’s Republic of China through Investment Development Path created by J.H. Dunning pointed out that between 2007 and 2009 PRC has moved rapidly from the second phase (value of FDI inflow is much larger than capital outflow) to the third stage, when the expansion of outward investments and slowing growth of inward FDI can be seen. That phase of economic development is characteristic, among other things, of new industrialized economies. Furthermore, keeping the present pace of growth, in 2011, the value of the Chinese foreign investments outflow can surpass the FDI inflow to China. As a result, China’s economy would be classified, based on the above-mentioned theory, as pertaining to the fourth stage, which is characteristic of developed countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 266-273
Keywords: China; FDI; outflow; Investment Development Path